2010
DOI: 10.1259/bjr/25629512
|View full text |Cite
|
Sign up to set email alerts
|

Vascular neck bruit in a teenager

Abstract: A healthy 16-year-old female presented to our internal medicine clinic with a 6-month history of dizziness and two fainting attacks within the past month. She mentioned feeling a buzzing noise in the left side of her neck, for which she sought medical advice. Physical examination revealed left carotid bruit but was otherwise unremarkable. Lipid profile and hypercoagulable screen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The angiographic appearance of this lesion is most akin to those described by Lipchik et al [2]. Qurash et al and Lenck et al have recently described similar diaphragm-like lesions, in which such concentric lesions were thought to be associated with a bruit and pulsatile tinnitus, respectively [3,4].…”
Section: Dear Editorsupporting
confidence: 60%
“…The angiographic appearance of this lesion is most akin to those described by Lipchik et al [2]. Qurash et al and Lenck et al have recently described similar diaphragm-like lesions, in which such concentric lesions were thought to be associated with a bruit and pulsatile tinnitus, respectively [3,4].…”
Section: Dear Editorsupporting
confidence: 60%
“…Cases of carotid web in the current literature present with the signs and symptoms common to all patients suffering acute embolic stroke regardless of etiology. 1,2,5,6 Factors that raise the suspicion of FMD or non-atherosclerotic carotid from atherosclerosis can be considered based on age and gender, where FMD occurs more frequently in younger individuals and women. 4 Race appears to be an equivocal factor.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional endarterectomy was performed in nearly all carotid web cases identified in the existing literature. [1][2][3][4][5][6][7] One notable exception was in a case where the web was identified in the vertebral artery, and the clinical team felt that the risk of surgical intervention was too high so the patient was treated with antiplatelet therapy. 3 Endarterectomy appears to be an effective treatment as several cases that reported outcomes suggested that the recovery was uneventful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations